Structural Performance Optimization of Multi-Story Steel Frames with Split-K EBF Bracing System Configuration - Kusuma, Kadek Adyatma Teja; Nindyawati, Nindyawati; Sulaksitaningrum, Roro; Muhammad, Dzul Fikri (INERSIA lnformasi dan Ekspose Hasil Riset Teknik Sipil dan Arsitektur, 2025)
Conventional steel frame structures tend to be susceptible to earthquakes, which can lead to significant economic and social losses. The earthquake disaster has motivated various technological exploration efforts to improve the seismic resilience of building structures. To strengthen the structure and prevent collapse, reducing the span length by adding bracing to the weak axis of the column proved effective. The addition of lateral stiffeners (bracing) to the elements of the frame structure is crucial in reducing lateral forces due to earthquakes in high-rise buildings. However, the researchers only focused on comparing the types of bracing used. Therefore, the purpose of this study is to optimize the structure of the steel frame multi-story building by innovating the configuration of bracing placement to match the composition of the building. To produce optimal results, the steel frame building model using bracing is varied in the placement of bracing with the middle model (BC1), the edge model (BC2), and the even model (BC3), so that the three models produce the effect of bracing placement on the building. The three building models will be analyzed using SAP200 to produce the performance of the steel frame building structure, including displacement, natural vibration periods, and base shear forces. From the overall analysis of the three models, it is shown that the evenness model (BC3) produces the most optimal structural performance. This is also shown by the fulfillment of all structural performance requirements based on the requirements of earthquake-resistant structures in SNI 1726-2019. The result of the buffer evenly provides a large displacement that occurs on the 3rd floor in the X direction which compared to other models has the smallest value, which is 20.13 mm. Based on the results of the analysis, it is known that the uniform model has the smallest natural vibration period value of 0.779 seconds in the X direction and has the largest dynamic shear force value in the X direction, which is 4823.74 kN. Therefore, it can be concluded that there is an effect of the placement of supports in steel frame multi-story buildings on the ability of the building structure with the even placement model (BC3) to produce the most optimal building design when compared to other building models.